2008
DOI: 10.1074/jbc.m709364200
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Functional Boundaries of the Gata2 Locus by Rescue with a Linked Bacterial Artificial Chromosome Transgene

Abstract: Transcription factor GATA-2 is vital for both hematopoietic progenitor cell function and urogenital patterning. Transgenic mapping studies have shown that the hematopoietic and urogenital enhancers are located hundreds of kbp 5 and 3 to the Gata2 structural gene, and both are vital for embryonic development. Because the size of mammalian genes, including all of their associated regulatory elements, can exceed a megabase, transgenic complementation in mice has, in specific instances, proven to be a formidable h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Dissociation curves were obtained to confirm the specificity of the amplified DNA. The primer sequences were 5'-AGCAAAGACCCCAACGAGAA-3' and 5'-GGCGGCGGTCACGAA-3' for EGFP (Harraghy et al, 2011), and 5'-CCATAGGCTTCACACCTTCCTG-3' and 5'-GCACTAACACTACCTTCCTCAACCG-3' for -actin as an endogenous control of two copies (Brandt et al, 2008). A standard curve for each gene was generated using serial dilutions of genomic DNA and we confirmed that amplification efficiencies of both primer pairs were similar (data not shown).…”
Section: Copy Number Determinationsupporting
confidence: 62%
See 1 more Smart Citation
“…Dissociation curves were obtained to confirm the specificity of the amplified DNA. The primer sequences were 5'-AGCAAAGACCCCAACGAGAA-3' and 5'-GGCGGCGGTCACGAA-3' for EGFP (Harraghy et al, 2011), and 5'-CCATAGGCTTCACACCTTCCTG-3' and 5'-GCACTAACACTACCTTCCTCAACCG-3' for -actin as an endogenous control of two copies (Brandt et al, 2008). A standard curve for each gene was generated using serial dilutions of genomic DNA and we confirmed that amplification efficiencies of both primer pairs were similar (data not shown).…”
Section: Copy Number Determinationsupporting
confidence: 62%
“…We purified the genome DNA from the tail of each line of mouse and performed qPCR using primers to amplify the EGFP gene. We also amplified the endogenous -actin gene as a control of two copies (Brandt et al, 2008) and the copy number of the transgene was calculated as a ratio to the control per copy. Ratios of EGFP to -actin per copy were 2.96 ± 0.80 for #528, 2.60 ± 0.56 for #531, 0.87 ± 0.30 for #542, 1.37 ± 0.55 for #566, 1.16 ± 0.39 for #675, and 1.38 ± 0.27 for #676 (Table1).…”
Section: Establishment Of Transgenic Lines and Determination Of Theirmentioning
confidence: 99%
“…More than a decade ago, we discovered that a 271-kbp Gata2 yeast artificial chromosome (YAC) transgene, which circumscribed genomic sequences from -198 kbp to +73 kbp (with respect to the translational start site) of the Gata2 locus, could fully rescue the embryonic lethality in Gata2 -/-embryos (3). Hence, this YAC functionally defined the genomic limits of the Gata2 locus that contained all of the regulatory element(s) required for fully elaborating primitive and definitive hematopoiesis, but the YAC only incompletely rescued all of the GATA-2 functions, since the P0 pups died from incomplete patterning of the urogenital system (3,9,20).…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of the start codon was also introduced in the first exon to initiate translation from the start codon of Cre cDNA. The recombinant BAC clone was confirmed by digestion and sequencing, and purified as circular BAC DNA by ultra centrifugation with caesium chloride 55 .…”
Section: Methodsmentioning
confidence: 99%